Clonning and characterization of alfa-globulin promoter into an expression vector - Mustafa, Abubakar Sadik (2013)
The world population is expected to rise by an addition of 2 billion by 2030 and rice consumers are projected to increase by 1.8% annually. Hence, rice production must be increased between 25-45% to match-up the growing population since it is a staple food to more than half of the world’s population. The manipulation of targeted gene in endosperm is a reliable tissue for the production of recombinant proteins over other tissues because it is more cost-effective, it is easier to scale-up agricultural yield, provides a larger storage ability and safe long-term storage. However only a few endosperm-specific promoters have been identified. The present research, successfully constructed the recombinant plasmid, pCAMGpro from the expression vector, pCAMBIA1305.2 containing the strong endosperm-specific a-globulin promoter (AsGpro). The AsGpro was successfully amplified from pmCACA:GFP using the forward primer, AsGproF_HindIII (5' CACAAACGTGCAAAAGCTTAATTCG 3') and the reverse primer, AsGproR_BamHI (5' GACGGATCCGAGATTGTAGAAGG 3') at 55°C. The size of the promoter fragment was approximately 848 bp. Sequencing and subsequent bioinformatics analysis, confirmed 98% homology of nucleotides to A. sativa (Glo1) gene, promoter region (Accession number: AY795082.1). This fragment was then cloned into pMR104a to generate the recombinant plasmid pMRGpro. Subsequent cloning of the recombinant cassette into the expression vector, pCAMBIA1305.2 to create the new recombinant plasmid, pCAMGpro was achieved. These finding can be used to genetically modify rice to express high levels of endosperm specific nutritional proteins of interest that would increase food production and help in alleviating the food crisis facing the world.